Revolução do consumo colaborativo - Bassani, Giovanni Goulart (Universidade do Vale do Rio dos Sinos, 2016)
This study aimed to identify the role and impact of industrial capitalism in today's society. From the need for a change in consumption habits, it was intended to map out how the collaborative economy can support sustainable development while minimizing environmental impacts, as well as presenting the main trends of sharing platforms such as economic development. The research had a qualitative approach and strategy as the interpretative phenomenological research method, which seeks an in-depth knowledge of a specific object, by collecting data with the interview technique. It was found that there is a need to adopt collaborative solutions as a way to improve the quality of life. In this context it is important to analyze the behavior of people and their engagement in the sharing of actions, which is growing rapidly boosting the economy by changing the consumption relationship between people, providing access to goods and services.
Keywords: Economia colaborativa; Consumo consciente; Impactos meio ambiente; Economia compartilhada; Collaboration; Shadow Economy; New Capitalism; Sustainability